Perbedaan Kadar Protein Asi pada Ibu dengan Gangguan Penyakit Anemia dengan Asi pada Ibu Normal - Nuzula Irfa Nuriana; Ulva Hari Andini (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Scientifically, the quality of human life can begin in the womb, namely in the first 1000 days, with details of 270 days in the womb, 730 days after the baby is born. So this period is a very vulnerable period in influencing children's growth and development. So maximum steps and efforts are needed to prevent malnutrition which has fatal consequences for the development of the baby, namely by paying attention to nutrition from the time the baby is in the womb, starting from pregnancy, breastfeeding until the child is 23 months old. However, the mother's condition has a big influence on the development of toddlers, especially mothers who are suffering from anemia, so it will be different from mothers who are in a healthy condition without (anemia). Comparative research was chosen in this article to obtain maximum results considering that this research focuses on 2 aspects that are compared scientifically. The results of this study show that there are quite large and high differences in the protein levels of breast milk from mothers who are in healthy condition, while breastfeeding mothers with anemia have low protein levels, which has the potential to cause malnutrition and impact on the baby's growth and development.